About an exalted tone that has recently risen in philosophy - Kant, Immanuel; Másmela Arroyave, Carlos (Estudios de Filosofía, 1991)
The name of philosophy, after having lost its first meaning, that of a scientific wisdom of life, has very soon come to be in demand as a title for the ornamentation of understanding in thinkers beyond the common, for whom philosophy now represents a kind of unveiling of a mystery. For the ascetics of the desert of Macario, philosophy was their monasticism. The alchemist was called philosophus per ignem. The lodges of ancient and modern times are adept at a mystery transmitted by tradition, of which they jealously wanted to reveal nothing (philosophus per initiationem.) Finally, the most recent possessors of such a mystery are those who have it in themselves, although unfortunately they cannot enunciate and communicate it universally through language (philosophus per inspirationem). But if there were a knowledge of the supersensible (which from the theoretical point of view is only a true mystery), which is possible to reveal perfectly in the human understanding from a practical point of view, said knowledge, by proceeding from this understanding as a The faculty of knowledge by concepts, however, would remain much inferior with respect to that which could be perceived immediately by the understanding as a faculty of intuition, because by means of the first knowledge, the discursive understanding has to devote a lot of work, first to the analysis and then to the composition of his concepts according to principles, and to climb with difficulty many rungs to make progress in knowledge, while an intellectual intuition would understand and present the object immediately and suddenly.